Third Five Year Plan Government of India : Planning Commission - Planning Commission (Planning Commission, 1960)
This Report sets out the objectives, policies and programmes of development for the Third Five Year Plan. Two Five Year Plans have helped strengthen the foundations of economic and social life and stimulated industrial and economic growth and scientific and technological advance. The Third Five Year Plan seeks to give a more precise content to the social objectives of the Constitution and represents a large advance towards their realisation. It takes account of the successes and the failures in the first two Plans and sets the tasks to be fulfilled in the perspective of development over the next fifteen years and more.
Government of India, Planning Commission